Selected Papers from IEEE ICASI 2019 - Chang, Shoou-Jinn; Young, Sheng-Joue; Prior, Stephen D.; Ji, Liang-Wen (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The 5th IEEE International Conference on Applied System Innovation 2019 (IEEE ICASI 2019, https://2019.icasi-conf.net/), which was held in Fukuoka, Japan, on 11-15 April, 2019, provided a unified communication platform for a wide range of topics. This Special Issue entitled "Selected Papers from IEEE ICASI 2019" collected nine excellent papers presented on the applied sciences topic during the conference. Mechanical engineering and design innovations are academic and practical engineering fields that involve systematic technological materialization through scientific principles and engineering designs. Technological innovation by mechanical engineering includes information technology (IT)-based intelligent mechanical systems, mechanics and design innovations, and applied materials in nanoscience and nanotechnology. These new technologies that implant intelligence in machine systems represent an interdisciplinary area that combines conventional mechanical technology and new IT. The main goal of this Special Issue is to provide new scientific knowledge relevant to IT-based intelligent mechanical systems, mechanics and design innovations, and applied materials in nanoscience and nanotechnology.